Upaya Peningkatan Mahir Berbahasa Arab melalui Program Mahasiswa KKN - Fuadi, Muhammad (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Since the discovery of COVID-19 in Indonesia which resulted in a global pandemic, many people have tried to play a role in resolving the existing problems. One of them is contained in thematic KKN activities, students serve in the community environment of Darullugha Wadda'wah Islamic Boarding School. Where in its implementation, it begins with conducting an initial survey in the area (to identify problems) and it is found that there are too many busy students and lack of free time to learn Arabic more proficiently. Therefore, an activity program of speaking Arabic fluently in 5 minutes. Although there are various problems, it is hoped that after the implementation of this activity the students' ability to speak Arabic can be more proficient in everyday life.